2020
DOI: 10.1063/5.0014519
|View full text |Cite
|
Sign up to set email alerts
|

Interactions at engineered graft–tissue interfaces: A review

Abstract: The interactions at the graft–tissue interfaces are critical for the results of engraftments post-implantation. To improve the success rate of the implantations, as well as the quality of the patients' life, understanding the possible reactions between artificial materials and the host tissues is helpful in designing new generations of material-based grafts aiming at inducing specific responses from surrounding tissues for their own reparation and regeneration. To help researchers understand the complicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 186 publications
0
3
0
Order By: Relevance
“…Successful integration of biomaterials with host tissues involves cell migration, maturation, and deposition of extracellular matrix components, and requires a continuous flow and exchange of nutrients, growth factors, signaling molecules, oxygen, and waste products. [ 69 ] In this case, interfacial adhesion plays an important role in supporting those interactions by ensuring a continuous contact at the biomaterial–tissue interface during the regeneration process. Yu et al reported that the use of a nonadhesive hydrogel resulted in an obvious gap between the hydrogel and native cartilage.…”
Section: The Need For Hydrogel–tissue Adhesionmentioning
confidence: 99%
“…Successful integration of biomaterials with host tissues involves cell migration, maturation, and deposition of extracellular matrix components, and requires a continuous flow and exchange of nutrients, growth factors, signaling molecules, oxygen, and waste products. [ 69 ] In this case, interfacial adhesion plays an important role in supporting those interactions by ensuring a continuous contact at the biomaterial–tissue interface during the regeneration process. Yu et al reported that the use of a nonadhesive hydrogel resulted in an obvious gap between the hydrogel and native cartilage.…”
Section: The Need For Hydrogel–tissue Adhesionmentioning
confidence: 99%
“…Zhu and colleagues provide a critical analysis on the complicated tissue reactions and tissue-biomaterial interactions following implantation, which is hoped to help the readership understand these cascades of events, allowing the development of better grafts possessing promoted biocompatibility and functions. 24 Pan and colleagues then, in another review, discuss polymer-based hydrogel biomaterials utilized towards hemostasis-control and wound-dressing. 25 Gao and colleagues further narrow down the scope by specifically describing stimuli-responsive and multi-functional hydrogels that are suitable for the management of diabetic wounds, 26 concluding the Special Topic.…”
Section: Functional Biomaterials Used Toward Wound Dressingmentioning
confidence: 99%
“…In the long term, such an interaction can affect the condition of the adjacent part of the body. The border of separation and contact between the implant and the tissue is important and various processes of both positive and negative nature can occur there [3,4]. Weak electromagnetic fields and radiation, under constant action, can also affect this process and even the immunity of the human body [5].…”
Section: Introduction Formulation Of the Problemmentioning
confidence: 99%